Determination of Packaging Design Elements of Baby Fish Crispy MSMEs Using Kansei Engineering Method - Sari, Novi Purnama; Fatah, Abdillah Nur; Amir, Anneke Hazima Putri; Rasyid, Akbar Fikri (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
The current packaging of baby fish crispy has problems, namely packaging design elements such as not having an identity on the packaging and the packaging becomes less attractive, making it difficult to compete with similar products. The research objective is to identify packaging design elements that are in accordance with consumer perspectives. The research method uses Kansei Engineering with the supporting method used is Quantification Theory Type-1 (QTT1), to analysis the interaction between design elements and design concepts by converting independent variable categories (design elements) into quantitative data in KE. The research results obtained 7 categories of design elements based on 42 predetermined samples. The selected concept ‘Standard - Protection’ obtained the highest R-Square value of 0.9909 with design elements namely: aluminum (X1.7), tall tube (X2.2), lift-off lid (X3.2), corporation & window (X4.9), modern (X5.1), large (X6.3), and direct printing (X7.2). The results of the priority of design elements obtained from the Partial Correlation Coefficient (PCC) value with the highest value on the concept of ‘Standard - Protection’ are the type of body design element (X2) with a value of 0.98598.